Production of tissue culture-derived planting materials of Musa acuminata cultivar Rastali and Lemak Manis / Nurulmanizar Mansor - Mansor, Nurulmanizar (Faculty of Plantation and Agrotechnology, 2019)
The production of Musa acuminata cultivar Rastali and Lemak Manis were tested on tissue culture technique. As we know, micropropagation is a method to produce genetically identical plantlets by using tissue culture techniques. The plantlets produced through this technology are true-to-type of the selected genotype. Tissue culture technique also produces plants free of disease. The aims of this study to produce banana planting material from sword sucker of Musa acuminata cultivar Rastali and Lemak Manis and to compare the regeneration efficiency of different banana cultivars in light and dark condition (24 hours). Explants from banana were surface sterilized with ethanol 70% and sodium hypochlorite 10%. After that, the explants from banana were cultured on MS medium supplemented with BAP (1mg/ml) and NAA (1mg/ml) under aseptic condition. Explants were located at light and dark condition to investigate the effect of light on the regeneration efficiency of the explants. Data collected and evaluate was performed to compare the shoot regeneration efficiency of Musa acuminata cultivars Rastali and Lemak Manis in tissue culture. Then, plantlets were transferred to the potting mix consisting soil (topsoil, sand, farm yard manure). Then, acclimatization of plantlets was carried out before to the field.